EDUCATIONAL METAVERSE PLATFORMS AS NEW LEARNING FRONTIERS: OPPORTUNITIES, RISKS, AND PEDAGOGICAL IMPLICATIONS - Loso Judijanto; Rustiyana Rustiyana; Nurul Saila (CV. ADIBA AISHA AMIRA, 2025)
This study explores the emerging role of educational metaverse platforms as transformative learning frontiers by synthesizing findings from recent literature on virtual, augmented, and immersive learning environments. Using a systematic literature review method, the research analyzes theoretical developments, empirical evidence, and pedagogical models that frame the integration of metaverse technologies into contemporary education. The findings reveal that educational metaverses offer significant opportunities for enhancing experiential learning, social presence, collaboration, and student engagement through immersive simulations and personalized learning pathways. However, the literature also highlights critical risks related to data privacy, digital inequality, cybersecurity, psychological effects, and pedagogical misalignment when immersive technologies are not implemented responsibly. The study further identifies important pedagogical implications, including the need for new instructional designs, teacher digital competencies, ethical guidelines, and inclusive access frameworks to ensure meaningful learning outcomes. Overall, the research contributes to a deeper understanding of how metaverse-based learning ecosystems can be developed and governed to support effective, equitable, and ethical education in the digital era.